(untitled) (ELS Journal on Interdisciplinary Studies in Humanities, 2018)
Construction type is a theory proposed by Dixon to analyze sentences based on its semantic type. This study aimed to compare the construction type of ‘deliver’ verb of English compared to ‘bawa’ verbof Wolio language proposed by Dixon and to elaborate the form of ‘bawa’ when it applied in different type of sentences. Generally, for Giving semantic type, there are four types of construction to cover it. There are some words includes in this Giving type and one of the words is ‘deliver’. Descriptive qualitative method is used to analyze this study. To do this study, the writer collects the data from COCA and or BNC for English data, while for Wolio data, the writer gained from observation and or interview. Furthermore, in his framework, ‘deliver’ constructed in construction type I only. Nevertheless, the result of this study shows that beside can be constructed in construction type I, the data from COCA and or BNC shows that ‘deliver’ also can be constructed in construction type II while the for the Wolio language, the data shows that there are two construction type which can be applied for the verb and Dixon’s framework does not cover it. Moreover, in Wolio language, the form of ‘bawa’ verb can be formed in ‘bawa’, ‘tobawa’, ‘bawea’, ‘bawapo’, ‘bawakea’, ‘bawakapea’, and ‘bawapea’.